TAMs-specific ARF1 inhibition reprograms glioma microenvironment and enhances the therapeutic effect of oncolytic adenovirus - Tao Cao; Tong Hao; Xiaoru Zhang; Bo Chen; Hongxuan Zhang; Luocheng Shao; Wenqiao He; Bingnan Li; Qihao Zheng; Peng Ji; Ke Tao (iScience)
Summary: Gliomas, characterized by their robust immunosuppressive microenvironment, pose a significant challenge to the efficacy of immunotherapies. The cGas/STING signaling pathway is emerging as a promising target for cancer immunotherapy. The inhibition of ADP-ribosylation factor 1 (ARF1), a pivotal regulator within cGas/STING signaling pathway, has been shown to enhance the activation cGas/STING. We investigated the impact of macrophage-specific ARF1 suppression on the phenotype of tumor-associated macrophages (TAMs) and the subsequent tumor specific immune response. Our findings reveal that targeted downregulation of ARF1 in TAMs substantially amplifies the immune response induced by oncolytic adenoviruses, effectively reprograms these macrophages, and bolsters anti-tumor immunity. The use of oncolytic adenoviruses armed with ARF1 knockdown elements has been demonstrated to exert a significant suppressive effect on glioma growth through the concerted action of multiple pathways and effectively elicit immune memory, thereby enhancing the survival rates of tumor bearing mice and preventing tumor recurrence.